Analisis Efisiensi Pengeluaran Anggaran Belanja Bidang Kesehatan dan Pendidikan Metode DEA 2021-2023 - Rahmawati, Ida; Muhsyaf, Saipul Arni (Jurnal Ilmiah Global Education, 2025)
The efficiency of government spending in the health and education sectors is a crucial factor in achieving sustainable development goals. This study analyzes the budget spending efficiency of provinces with a high Human Development Index (HDI) in Indonesia during the 2021-2023 period using the Data Envelopment Analysis (DEA) method with the Constant Return to Scale (CRS) approach, and an input-oriented perspective. The input variables include budget allocation and resources (medical personnel for health; number of schools for education), while the output variables consist of performance indicators such as Life Expectancy, Maternal/Infant Mortality Rates (health), and Literacy Rate and Years of Schooling (education). The results of the study show variations in efficiency achievements across provinces. Riau and the Riau Islands consistently achieved perfect efficiency (score 1) in both sectors, while provinces such as DI Yogyakarta and East Kalimantan experienced inefficiencies, with the education sector being more stable than health. These findings indicate the need for optimization of budget allocation, human resource capacity building, and the application of technology to enhance efficiency, particularly in the health sector. This study provides empirical contributions to fiscal effectiveness and policy recommendations to strengthen regional budget management. The implications of the research include the importance of data-based monitoring systems, inter-provincial benchmarking, and multi-stakeholder collaboration to ensure sustainable human development.